THE ABILITIES, VALUES AND STRATEGIES ENCOURAGED BY THE UNIVERSITY TEACHING STAFF: AN ANALYSIS ACCORDING TO SUBJECT AREA, TEACHING EXPERIENCE AND GENDER - Aciego de Mendoza, Ramón; Martín Cabrera, Eduardo; Domínguez Medina, Raquel (Anales de Psicología / Annals of Psychology, 2003)
The following is an analysis of what the university teaching staff have reported to be the abilities, values and strategies that they encourage in their pupils as well as those areas, which are considered to be equally important, but which the staff admit they overlook or do not know how to do so. The information has been gathered from questionnaires sent by e-mail to all of the teaching staff at the University of La Laguna. 164 lecturers responded to the questionnaires. The results showed that the university teaching staff feel that they are capable of helping their pupils to understand the subject matter but that they have difficulty in helping the students to build on the subject matter that has been taught and to produce fluent, wellfounded discourse. In the education of values the university teaching staff find it easier to promote values of efficiency than values of personal and social development. A differential analysis is then made of the results according to sex, years of teaching experience and the lecturer’s subject area.